2013
DOI: 10.18052/www.scipress.com/ilcpa.17.82
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrical Performance of DSSC by Co-Doped SnO<sub>2</sub> Nanoparticles

Abstract: Investigation of the I-V characteristics of the DSSC based on interconnected with cobalt-doped SnO 2 nanoparticles covered with a nano-scale thin layer which was absorbed by natural dyes are described. The presence of co-doped SnO 2 has been confirmed by its characteristic XRD pattern and the shape of the particle is confirmed by SEM. The thickness of the protective layer can be conveniently controlled by the mole value of co-doped SnO 2 used in the preparation of the thin film and the optimum conditions for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The broad band appeared in the range of 3500 to 3200 cm -1 and the peak appeared in 2800 cm -1 are may be due to the vibration of water molecule. The peaks appeared at 2330 cm -1 1608 cm -1 are related to the O-H stretching due to the absorbed water on the surface [13][14].There is a small shift occurs in the peak position. This is for the reason that there is a difference in bond length due to the replacement of Co ions in Sn site of the SnO 2 lattice.…”
Section: Xrd Spectrum Analysismentioning
confidence: 95%
“…The broad band appeared in the range of 3500 to 3200 cm -1 and the peak appeared in 2800 cm -1 are may be due to the vibration of water molecule. The peaks appeared at 2330 cm -1 1608 cm -1 are related to the O-H stretching due to the absorbed water on the surface [13][14].There is a small shift occurs in the peak position. This is for the reason that there is a difference in bond length due to the replacement of Co ions in Sn site of the SnO 2 lattice.…”
Section: Xrd Spectrum Analysismentioning
confidence: 95%
“…It can be noted from Table 1 that SnO 2 was employed as photoanode instead of TiO 2 in the cell having chlorophyll extracted from Coccinia indica (ivy gourd) leaves [32]. Comparison with TiO 2 revealed that SnO 2 is chemically stable and has larger bandgap of 3.6 eV and higher electron mobility [49,50].…”
Section: Performance Of Chlorophyll-sensitized Dsscsmentioning
confidence: 99%
“…SnO 2 having high electron mobility can yield fast electron transport and therefore electron recombination can be decreased. From the table, the cells with chlorophyll from C. indica leaves exhibited the efficiencies of 0.260, 0.290, and 0.310% using three photoanodes, that is, SnO 2 , La-doped SnO 2, and La-Cu-doped SnO 2 , respectively [32]. Doping elements into DSSC photoanode improved the performance since more dye molecules can be adsorbed in the working electrode due to larger surface area owing to increased roughness and pores after doping [52].…”
Section: Performance Of Chlorophyll-sensitized Dsscsmentioning
confidence: 99%